Correlative light and electron microscopy III - Müller-Reichert, Thomas; Verkade, Paul (Methods in cell biology, 2017)
Front Cover -- Methods in Cell Biology -- Series Editors -- Methods in CellBiology: Correlative Light and Electron Microscopy III -- Copyright -- Contents -- Contributors -- Preface: The Key Lies in the Right Combination -- 1 - Millisecond time resolution correlative light and electron microscopy for dynamic cellular processes -- INTRODUCTION -- 1. METHODS -- 1.1 Chlamydomonas reinhardtii Culture -- 1.2 Imaging and Embedding Chamber Preparation -- 1.3 Light Microscopy -- 1.4 Sample Preparation for Electron Microscopy -- 1.4.1 Chemical postfixation and embedding -- 1.4.2 Thin sectioning -- 1.4.3 Staining of the sections and application of fiducial markers -- 1.5 Electron Tomography -- 1.6 Registration of Light and Electron Microscopy Images -- 1.7 Data Analysis -- 1.8 Preparation of Flagellar Cross Sections for Correlative Light and Electron Microscopy Analysis -- 2. INSTRUMENTATION AND MATERIALS -- 2.1 Chlamydomonas reinhardtii culture -- 2.2 Imaging and Embedding Chamber Preparation -- 2.3 Light Microscopy -- 2.4 Sample Preparation for Electron Microscopy -- 2.4.1 Chemical postfixation and embedding -- 2.4.2 Thin sectioning -- 2.4.3 Staining of the sections and application of fiducial markers -- 2.5 Electron Tomography -- 2.6 Registration of Light and Electron Microscopy Images -- 2.7 Data Analysis -- 2.8 Preparation of Flagellar Cross Sections for Correlative Light and Electron Microscopy Analysis -- 3. DISCUSSION AND OUTLOOK -- Acknowledgments -- REFERENCES -- 2 - 3D subcellular localization with superresolution array tomography on ultrathin sections of various species -- INTRODUCTION AND RATIONALE -- 1. METHODS-CORE PROTOCOL -- 1.1 High-Pressure Freezing -- 1.2 Freeze Substitution -- 1.3 Embedding -- 1.4 Ultramicrotomy -- 1.5 Light Microscopy -- 1.6 Contrasting and Carbon Coating -- 1.7 Scanning Electron Microscopy